Sistem Pengaduan Masyarakat Berbasis Web menggunakan Metode Waterfall - Eka Damayanti; Wisnu Sanjaya; Fera Tri Wulandari (JITU : Journal Informatic Technology And Communication, 2023)
Kragilan Village is one of the villages in Mojosongo District, Boyolali Regency, Central Java. The obstacle experienced by Kragilan Village is in community complaints which are still carried out conventionally. In this way, the community must come directly to the Village office to submit complaints and in this case it is less effective because the complaint file can be lost and damaged. So to accommodate all complaints from the public, it is necessary to have a system that is made to make it easier for the community to express their aspirations in an easy way and can be used whenever the community needs it. The design of this system uses the UML (Unified Modeling Language) model, namely use case diagrams, activity diagrams, sequence diagrams, and class diagrams. At the development stage of this system using the Codeigniter framework, and a MySQL database with the Waterfall system development method. . This system has been tested by testing Black Box testing and beta testing through questionnaires to website users. The results of the Black Box test show that the function on this website system as a whole has been running well without any errors.